2021
DOI: 10.3390/pharmaceutics13081149
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Laser Speed and Drug Particle Size on Selective Laser Sintering 3D Printing of Amorphous Solid Dispersions

Abstract: This research demonstrates the influence of laser speed and the drug particle size on the manufacturing of amorphous solid dispersions (ASD) and dosage forms thereof using selective laser sintering 3-dimensional (3D) printing. One-step manufacturing of ASD is possible using selective laser sintering 3D printing processes, however, the mechanism of ASD formation by this process is not completely understood and it requires further investigation. We hypothesize that the mechanism of ASD formation is the diffusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…Promising new advancements such as EBM [205] for metal printing to the use of bioactive coatings [204], antimicrobials, and even drug delivery methods for PBF [206][207][208][209][210][211], will ensure that novel implants can be provided to patients in a timely manner, with the appropriate legislation and oversight from government and regulators. In creating these personalized implants, humans will be equipped with the necessary tools to mitigate the impact of bone-related illnesses and the overall disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…Promising new advancements such as EBM [205] for metal printing to the use of bioactive coatings [204], antimicrobials, and even drug delivery methods for PBF [206][207][208][209][210][211], will ensure that novel implants can be provided to patients in a timely manner, with the appropriate legislation and oversight from government and regulators. In creating these personalized implants, humans will be equipped with the necessary tools to mitigate the impact of bone-related illnesses and the overall disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…This is because unlike photoabsorbing polymers such as polyamides (PA-12) designed for SLS printing in the case of pharmaceutical blends where polymers do not absorb the laser directly, photoabsorbing species like Candurin acts as a conducting excipient, which, in turn, causes the thermal transition of the polymer, resulting in sintering. 27 Thereby increasing the amount of Candurin at the cost of Kollidon VA 64 led to a reduction in the hardness and weight of the printlet. These findings add to the current understanding of the SLS process because properties such as weight critically influence the dose of the printlet and hardness impacts the stability and performance of the dosage forms.…”
Section: Discussionmentioning
confidence: 99%
“…For this experiment, the polymerʼs absorbance was not evaluated, as previous studies have demonstrated that it does not absorb visible radiation. 18,27 2.2.2. Critical Parameter Determination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the combined application of heat and laser energy during the SLS process, an increased localised temperature first causes a sintering of the polymer and drug particles, followed by a rapid cooling to the surface temperature of the printer, which maintains the drug as intertwined in the polymer matrix in an amorphous form. Indeed, to date, a wide range of drugs, including paracetamol [ 22 , 23 ], ritonavir and copovidone [ 24 ], lopinavir [ 25 ], ibuprofen [ 26 ], indomethacin [ 27 ], ondansetron [ 28 ], and diclofenac sodium [ 29 ], as well as amlodipine and lisinopril [ 30 ], have been converted to a full or partial amorphous form post-printing using SLS technology.…”
Section: Introductionmentioning
confidence: 99%